An Observational Study to Assess the Probable Exciting Factors (Mental /Emotional) Triggering the Physical Manifestations of Psoriasis in 20-60 Years Aged Patients. (Advancements in Homeopathic Research, 2025)
Background-Skin is the mirror of internal health,  any disturbance in here reflects on skin which is very  worrying. Psoriasis is one of the non communicable  chronic skin disease. Though non fatal bur its  recurrence and complications make people suffer a  lot. The real cause is yet to be discovered. A study  conducted on global burden of disease in 2010 and  2014 showed that 4th leading cause of non-fatal  morbidity were skin diseases worldwide. Objective-Present study is an attempt-to understand  the mental/emotional factors which trigger/aggravate  the psoriasis.  Methodology-Purposive sampling method was  used to select subjects based on inclusion/exclusion  criterion. A detailed individual case taking was done  to understand the triggering/aggravating factors at  mental/emotional level.  Results-In this study it was found that loss of loved  ones (20%) and suppressed anger (20%) as a main  triggering factors. The most common age group  affected was 21-30years (40%),  Conclusion-though with this we cannot conclude  these are the sole triggering factors, there may be  more as in homoeopathy advocates individualization  as one of the basic fundamental principles, and it is  recommended to study with large samples.
Keywords: Mental/Emotional triggers; Physical manifestations of Psoriasis; Psoriasis; Triggering factors for Psoriasis